1994
DOI: 10.1159/000177810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Dietary Calcium on Quantitative and Qualitative Fecal Fat Excretion in Man

Abstract: Oral calcium supplementation is thought to be a useful interventional agent to decrease colon cancer risk. This is supposedly due, at least in part, to the binding of bile acids and fatty acids by calcium in the colon, thus prohibiting the damaging effects of these substances to the epithelium. To determine the effects of calcium supplementation on fecal fat excretion, 24 subjects kept a fat and calcium constant diet for one week and were supplemented with either 0, 2 or 4 g elemental calcium as calcium carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
6
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 14 publications
4
62
6
8
Order By: Relevance
“…Serum lipid levels have also an important role in the calcium metabolism. As previously described, calcium intake affects the body mass index (BMI) in different ways, the easiest of which, is the inhibition of lipid and free fatty acid absorption [13]. It seems that the most important effect of calcium is on the extracellular calcium control.…”
Section: Discussionmentioning
confidence: 97%
“…Serum lipid levels have also an important role in the calcium metabolism. As previously described, calcium intake affects the body mass index (BMI) in different ways, the easiest of which, is the inhibition of lipid and free fatty acid absorption [13]. It seems that the most important effect of calcium is on the extracellular calcium control.…”
Section: Discussionmentioning
confidence: 97%
“…6-8, 16 Shahkhalili et al 8 showed, in a crossover study, that supplementation of chocolate with 0.9W% calcium, as part of a diet providing 14E% protein and 39E% fat, resulted in a two-fold increase in total fecal fat excretion (4.4-8.4 g/day). This is somewhat similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with CaP has been shown to increase fecal fat excretion in rats and humans, probably through the formation of calcium soaps. 46,47 We cannot exclude that part of the effect of Orl and of CaP is based on the formation of calcium-fatty acid soaps and subsequent capture of UCB by these soaps. The low efficacy of CaP treatment during a HF diet, however, suggests that other mechanisms must be involved.…”
Section: Discussionmentioning
confidence: 99%